Genistein Enhances the Efficacy of Cabazitaxel Chemotherapy in Metastatic Castration-Resistant Prostate Cancer Cells - Zhang, Shumin (Prostate, 2013)
BACKGROUND: Cabazitaxel (Jevtana) has been approved for the treatment of metastatic castration-resistant prostate cancer (mCRPC). However, most patients progress and become chemoresistant, which remains a major challenge in the management of advanced PCa. In this study, we investigated whether genistein, an isoflavone abundant in soy products, could sensitize mCRPC cells to cabazitaxel treatment in experimental models. METHODS: The in vitro and in vivo effect of genistein in enhancing the response of mCRPC cells to cabazitaxel chemotherapy was evaluated in experimental models. RESULTS: Genistein increases the expression of pro-apoptotic protein Bax, activates apoptotic signals, and enhances the response to cabazitaxel treatment in mCRPC cells. In a PC3-luciferase xenograft model, the combined treatment with genistein and cabazitaxel significantly retarded the growth of mCRPC when compared to vehicle control, cabazitaxel, or genistein. Tissue staining confirmed the in vivo effect of genistein on the induction of Bax and activation of apoptosis. CONCLUSION: This study provided the first preclinical evidence supporting that genistein could be beneficial in improving cabazitaxel chemotherapy in mCRPC.